Antipodal Vivaldi Antenna for Water Pipe Sensor and Telemetry - Giuseppe Ruvio; Domenico Gaetano; Max J. Ammann; Patrick McEvoy (International Journal of Geophysics)
An antipodal Vivaldi antenna operates simultaneously for telemetry and sensing when placed conformally onto PVC pipes. Good radiation efficiency is realised and the antenna impedance matching remains stable when a pipe is empty or contains water. The fidelity factor performance based on an input Ultra-Wideband Gaussian pulse is a suitable figure of merit to detect water presence. Different water levels and pipe conditions correspond to fidelity factors between 90% and 96%, which are a suitable dynamic range for sensing and the appropriate quality for pulse communications for remote monitoring.